Modeling Wave Energy Dissipation by Bottom Friction on Rocky Shores - César Acevedo-Ramirez; Olavo B. Marques; Falk Feddersen; Jamie H. MacMahan; Sutara H. Suanda (Journal of Marine Science and Engineering, 2026)
Rocky shores are characterized by rough, multi-scale bathymetric variations that result in enhanced wave energy dissipation by bottom friction compared to sandy beaches. Realistic SWAN simulations of surface gravity waves across the rocky shores of Monterey (CA, USA) are conducted, and model results are compared to 20 inner-shelf observational sites spanning 34–5 m water depth. The wave field was highly variable during the study, including alternately low energy waves dominated by southern swell and higher energy local waves aligned with strong north-westerly winds. Including a modified bottom friction parameterization is required for the model to reproduce bulk wave statistics with high skill across the entire inner shelf. The SWAN simulation with the default bottom friction parameterization overestimates significant wave height relative to observations because the friction factor fe parameterization has a maximum value of 0.3. Additional simulations included two empirical formulations relating fe to the normalized wave excursion Ab/kN in the large roughness regime Ab/kN

Physical and biological processes underlying the sudden surface appearance of a red tide in the nearshore - Melissa M. Omand; James J. Leichter; Peter J. S. Franks; R. T. Guza; Andrew J. Lucas; Falk Feddersen (Limnology and Oceanography, 2011)
The sudden appearance at the surface of an alongshore‐parallel band of red tide near Huntington Beach, California, is described in high spatial and temporal resolution using novel instrumentation including a global positioning system–tracked jet‐ski. The scale of the surface chlorophyll a (Chl a ) band was small (~ 200 m cross‐shore) and ephemeral (3 h) compared with the subsurface extent of the red tide (~ 2 km, > 7 d). The red tide was dominated by the regionally common dinoflagellate Lingulodinium polyedrum (F. Stein) and had developed as a subsurface Chl a layer during the 7 d prior to the surface appearance. A few hours before the surface appearance, a subsurface patch of elevated Chl a (Chl a > 30 μg L −1 ) was observed in 13‐m total depth in the trough of a shoreward‐propagating internal wave, consistent with dinoflagellate vertical swimming interacting with the internal wave‐driven convergence. Internal wave‐breaking–induced vertical mixing in ~ 8‐m water depth vertically spread the Chl a patch to the surface, creating the alongshore surface band ~ 500 m from shore. Both the subsurface Chl a patch and the surface Chl a band were prevented from entering the surf‐zone by a density barrier of warm water adjacent to the beach. These high‐resolution observations emphasize the role of nearshore physical dynamics in controlling the duration and intensity of red tide exposure to coastal habitats.

Measuring Fluorescent Dye in the Bubbly and Sediment-Laden Surfzone - David B. Clark; Falk Feddersen; Melissa M. Omand; R. T. Guza (Water, Air, & Soil Pollution, 2009)